Lavandula austroapennina and Lavandula angustifolia essential oils and bioactive components: in vitro anti-denaturation effect of lavender from the Pollino massif (Southern Italy). (4th March 2023) - Conforti, Filomena; Perri, Maria Rosaria; Guerrini, Alessandra; Sacchetti, Gianni; Statti, Giancarlo
Abstract: The Mediterranean basin represents a rich source of medicinal and aromatic plants. These species contain different metabolites such as phenolics, flavonoids, tannins, coumarins and sterols known for their beneficial properties. The essential oils (EOs) of Lavandula austroapennina and Lavandula angustifolia from the Pollino massif (southern Italy) were characterized using gas chromatography-mass spectrometry and their anti-denaturation effect was assessed using in vitro models with heat-treated bovine serum albumin (BSA) chosen as a protein model. L. austroapennina EO showed a better in vitro anti-denaturation activity compared to L. angustifolia, with IC50 values equal to 260.4 ± 4.2 and 480.0 ± 2.6 µg/mL, respectively. In order to relate the observed results to the most interesting identified phytochemicals, some major components were also tested. Linalool and terpinen-4-ol proved to be effective in protecting BSA from heat denaturation. Moreover, the inhibitory properties on nitric oxide production were verified in lipopolysaccharide (LPS)-stimulated RAW 264.7 macrophages. Both lavender EOs showed concentration-dependent inhibitory properties, as well as the monoterpene linalool. Taken together, these results suggest that L. austroapennina EO and its main constituent linalool could be good candidates for further investigations, aimed at finding new drugs with anti-arthritic potential.